Proposed Improvement of Learning Course Development in Digital Telecommunication Company - Nafila, Revina Nida; Yudoko, Gatot; Sulyani, Agnesia Candra; Alberto, Richard (Journal Research of Social Science, Economics, and Management, 2025)
PT Digital Telecommunication Company (DTC) is a telecommunication company in Indonesia that is currently facing dynamic and competitive challenges in the telecommunication industry. The Corporate University Center (CUC), a support unit of PT DTC, is dedicated to enhancing the skills and knowledge of PT DTC employees in order to help the company achieve its strategic goals. Thus, CUC has developed Rencana Jangka Panjang Perusahaan (RJPP) 2025-2027 to continuously support the company strategy in the area of people development. Therefore, it is crucial to identify potential areas of improvement to ensure that CUC can effectively contribute to the success of PT DTC’s new strategy direction. This study focuses on the Learning Team at CUC, which aims to produce learning materials that enhance employee capabilities. To analyze this process, the study uses the ADDIE and Project Management framework to identify the operational process of learning design & development. By using the frameworks, CUC is expected to deliver high-quality learning materials that align with the company strategy effectively. Data collection is conducted by semi-structured interviews with five participants from the learning team, to explore the business strategy of the company and the day-to-day learning operations. The data was analyzed using NVivo 15 software, which generated word frequency queries to identify emerging themes. These themes were further analyzed through quotation analysis understand the contextual situation in the learning process. Data analysis results revealed six areas of improvement: Resource Management, Scalability Planning for High-Impact programs, Stakeholder Communication, Learner Participation, Learning Impact Measurement, AI Technology Enhancement.